A case report of remission of refractory membranous nephropathy progressing to stage 4 chronic kidney disease using low-dose rituximab: A long-term follow-up. Issue 25 (June 2018) - Zhou, Xu-Jie; Zhou, Fu-De; Wang, Su-Xia; Zhao, Ming-Hui
Abstract: Rationale: As suggested by the 2012 KDIGO guidelines, persistent elevation of serum creatinine > 3.5 mg/dl (> 309 μmol/l) (or an estimated glomerular filtration rate < 30 ml/min per 1.73 m 2 is one of contradictions for the use of immunosuppressive therapy in membranous nephropathy. Patient concerns: A 45-year-old man with membranous nephropathy negative for serum anti-phospholipase-A2-receptor antibody, showed no response to corticosteroids and cyclophosphamide. He progressed to chronic kidney disease stage 4 (CKD4) under tacrolimus and relapsed after withdrawal. Diagnoses: The patient received repeated renal biopsy, comfirming the diagnosis of membranous nephropathy with progressive glomerular and tubulointerstitial scarring. Interventions: He was treated with successfully four times with lose-dose (180 mg/m 2 every 2-3 months) rituximab (RTX) depending on his B cell counts, aiming to remain at 0-5 cells/μl. Outcomes: The patient was followed-up for almost 6 years. He achieved a partial remission at 11 months and a complete remission of the nephritic range of proteinuria at 34 months following infusion of RTX. RTX was well tolerated and the patient's renal function improved. He had no edema and his dosage of corticosteroids could be discontinued. Lessons: This case strongly suggested that rituximab has promising therapeutic significance, even in patients progressing to CKD4.